Photocatalytic Removal Of Methylene Blue From Aqueous Solution By Ag And La Doped Tio2 And Zeolite Supported Tio2 Under Visible Light - Us Saqib, Najm (2017)
In the present study titanium dioxide (tio2) nanoparticles (nps) were modified via ag, la and ag-la doping using low cost and facile liquid impregnation (li) method, immobilization on zeolite, and at different calcination temperatures (500, 700 and 900 °c). The unsupported tio2 nps (tio2, ag/tio2, ag-la/tio2, and la/tio2) prepared at different calcination temperatures, showed dominant anatase phase (96 to 98 wt%), reduction of band gap energy from 3.2 to 2.88 ev, and phpzc between 6.2 to 7.3. The zeolite supported samples (z@tio2, z@ag/tio2, z@ag-la/tio2, and z@la/tio2) prepared at different calcination temperatures, showed the appearance of rutile and brookite phases which reached up to 20 wt% with the increase in calcination temperature, less reduction in band gap energy (3.11 to 2.90 ev) and higher ph/>zc values (7.1 to 7.8) as compared to the unsupported tio2 nps. The photocatalytic degradation of mb by unsupported and zeolite supported tio2 nps were performed under normal laboratory condition which is at ambient ph, room temperature (25±2 °c) and compact fluorescent light.